Quantitative assessment of redness in Asian patients with recurrent blepharitis: the utility of cross-polarized light - Yue Tan; Yue Tan; Wenjia Sun; Yue Yin; Yue Yin (Frontiers in Medicine)
PurposeTo establish an objective and quantitative method of evaluation redness in patients with blepharitis.Methods12 adult Asian patients with recurrent blepharitis were enrolled in the case group. 24 healthy controls, matched for age and gender in a 1:2 ratio, were recruited as the health group. Population characteristics, related medical histories and clinical indices of both groups were recorded. Redness area proportion of eyelid (RAE%) and eyelid margin (RAM%), were evaluated by cross-polarized light (Vplus®) and image processing. Samples of eyelid margin secretions were collected for proteomics.ResultsThe population characteristics and clinical indices of two groups adhered to the study design. The score chart of principal component analysis shows significant differences in protein expression of eyelid secretions between two groups. The mean ± SD (standard deviation) values of RAE% and RAM% in the health group were 1.88 ± 2.53% and 1.63 ± 2.04%, respectively. The case group had the RAE% of 6.54 ± 7.20% (mean ± SD) and the RAM% of 17.14 ± 18.90% (mean ± SD), which were both significantly higher than those in the health group (all P < 0.05). Within the case group, RAM% was significantly higher than RAE% (P = 0.019), which means the redness in case group being concentrated within eyelid margin rather than the whole eyelid. RAM% had higher positive correlation coefficients with cornea staining, meibum quality, and meibomian gland dropout compared to RAE%. And RAM% was also positively associated with more protein expression levels in eyelid margin secretions.ConclusionBy using cross-polarized light, characteristic changes of redness can be observed in patients with recurrent blepharitis. RAM%, has a great potential value for standardizing and quantifying the inflammatory status of blepharitis.